Neutrophil granulocyte derived MMP-9 is a VEGF independent functional component of the angiogenic switch in pancreatic ductal adenocarcinoma - Bausch, Dirk; Pausch, Thomas; Krauß, Tobias; Hopt, Ulrich T.; Fernandez-del-Castillo, Carlos; Warshaw, Andrew L.; Thayer, Sarah P.; Keck, Tobias (Angiogenesis, 2011)
Vascular endothelial growth factor (VEGF) that is secreted by tumor cells plays a key role in angiogenesis. Matrix metalloproteinase 9 (MMP-9) is produced by inflammatory cells, such as stromal granulocytes (PMN), remodels the extracellular matrix and is known to promote angiogenesis indirectly by interacting with VEGF. The aim of this study was to determine the role of PMN-derived MMP-9, its interaction with VEGF, and the efficacy of anti-angiogenic therapy targeting MMP-9 with oral Doxycycline and VEGF with Bevacizumab in pancreatic cancer (PDAC).